An open microfluidic coculture model of fibroblasts and eosinophils to investigate mechanisms of airway inflammation - Zeng, Yuting; Su, Xiaojing; Takezawa, Meg G.; Fichtinger, Paul S.; Lee, Ulri N.; Pippin, Jeffery W.; Shankland, Stuart J.; Lim, Fang Yun; Denlinger, Loren C.; Jarjour, Nizar N.; Mathur, Sameer K.; Sandbo, Nathan; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Interactions between fibroblasts and immune cells play an important role in tissue inflammation. Previous studies have found that eosinophils activated with interleukin-3 (IL-3) degranulate on aggregated immunoglobulin G (IgG) and release mediators that activate fibroblasts in the lung. However, these studies were done with eosinophil-conditioned media that have the capacity to investigate only one-way signaling from eosinophils to fibroblasts. Here, we demonstrate a coculture model of primary normal human lung fibroblasts (HLFs) and human blood eosinophils from patients with allergy and asthma using an open microfluidic coculture device. In our device, the two types of cells are in two-way paracrine signaling via the shared media while being physically separated by a half wall. Initially, we assessed the level of eosinophil degranulation by their release of eosinophil-derived neurotoxin (EDN). Next, we analyzed the inflammation-associated genes and soluble factors using reverse transcription quantitative polymerase chain reaction (RT-qPCR) and multiplex immunoassays, respectively. Our results suggest an induction of a proinflammatory fibroblast phenotype of HLFs following the coculture with degranulating eosinophils, validating our previous findings. Additionally, we present a new result that indicate potential impacts of activated HLFs back on eosinophils. This microfluidic coculture platform provides unique opportunities to investigate the intercellular signaling between the two cell types and their roles in airway inflammation and remodeling.